2022
DOI: 10.1002/lt.26512
|View full text |Cite
|
Sign up to set email alerts
|

Donor eligibility criteria and liver graft acceptance criteria during normothermic regional perfusion: A systematic review

Abstract: Acceptance of liver grafts from donations after circulatory death (DCD) largely remains a “black box,” particularly due to the unpredictability of the agonal phase. Abdominal normothermic regional perfusion (aNRP) can reverse ischemic injury early during the procurement procedure, and it simultaneously enables graft viability testing to unravel this black box. This review evaluates current protocols for liver viability assessment to decide upon acceptance or decline during aNRP. The Preferred Reporting Items f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The possibility to expand the graft utilization with additional NMP requires the definition of universally accepted selection parameters with the highest possible specificity, while we still rely on center‐based viability criteria. Considering our experience, another potential limitation to NMP‐facilitated assessment of uDCD liver grafts is the lack of biliary assessment, but recent data showed that these patients have a very low risk of IC and a much higher risk of graft loss in the early perioperative period 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The possibility to expand the graft utilization with additional NMP requires the definition of universally accepted selection parameters with the highest possible specificity, while we still rely on center‐based viability criteria. Considering our experience, another potential limitation to NMP‐facilitated assessment of uDCD liver grafts is the lack of biliary assessment, but recent data showed that these patients have a very low risk of IC and a much higher risk of graft loss in the early perioperative period 7 …”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the most frequent approach to facilitate uDCD LT is sequential combination of pre‐procurement NRP and end‐ischemic, ex‐situ HMP. This strategy is based on the advantages of either technology in ensuring graft viability in the presence of long WIT (up to 170 min) and can overturn some limitations of uDCD 4,6,7 . In this scenario, graft selection is usually based on integration of NRP data (as per flow rate), metabolic parameters (lactate clearance), surrogate markers of liver injury (transaminases), and liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During NRP, the abdominal organs release the well-known proinflammatory molecules of IRI, and some are used to assess and predict the liver performance after later implantation [ 112 , 117 ]. In addition to liver macroscopy and biopsy, perfusate lactate and transaminases are routinely measured with various guidelines in different countries [ 116 , 120 ].…”
Section: The Impact Of Dynamic Organ Perfusion Strategiesmentioning
confidence: 99%